Psychometric Properties of the Chinese Version of the Brief State Rumination Inventory - Wang, Chanyu; Song, Xiaoqi; Lee, Tatia M. C.; Zhang, Ruibin (Frontiers in Public Health, 2022)
State rumination, unlike trait rumination which is described as a persistent and stable response style, is usually triggered by a specific stressful event and causes negative emotions within a short period of time. The measurement methods of trait rumination, such as the Ruminative Response Scale (RRS), are therefore not fully applicable to state rumination. Recently, researchers have developed the Brief State Rumination Inventory (BSRI) to characterize state rumination, addressing the gap in the field of accurate measurement of state rumination. In order to develop such an effective tool in the Chinese context, we developed a Chinese version of the BSRI and tested its psychometric properties. Two studies were conducted to address the research goal. In Study 1, we recruited 512 subjects, each of whom completed the Chinese version of the BSRI, RRS, Emotional Regulation Questionnaire (ERQ), Depression–Anxiety–Stress Scale (DASS), and Positive and Negative Affect Scale (PANAS). Results showed that the scores of the BSRI were positively correlated with all other scale scores (Ps<0.001), and the correlation with the RRS was the highest, indicating that the BSRI showed good convergent validity. Additionally, the Cronbach’s alpha coefficient for the Chinese version of the BSRI was 0.93. Study 2 aimed to examine the ecological validity of the Chinese version of the BSRI. We recruited another 54 subjects who were randomly divided into two groups, with 27 in the rumination induction group and 27 in the distraction group, and recorded the BSRI scores of the two groups before and after a specific experiment. We found there was a significant increase in BSRI scores after rumination induction (t=3.91, p<0.001), while there was no significant difference in the concrete distraction group before and after the experiment (t=0.70, p=0.48). In sum, the Chinese version of the BSRI showed good reliability and validity for assessing state rumination in the Chinese context.